2021
DOI: 10.25259/sni_362_2021
|View full text |Cite
|
Sign up to set email alerts
|

Eagle syndrome presenting as a neurological emergency: A case report

Abstract: Background: Eagle syndrome, due to the elongation of the styloid process as well as the calcification of the stylohyoid ligament, rarely presents itself with a major neurological disorder such as a brain infarct. Case Description: Authors describe the case report of a previously healthy 64-year-old Caucasian male that complained of inability to control his right upper and lower extremity of an acute nature. Imaging at the emergency department (magnetic resonance of the brain and computerized angiography) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The demographic, clinical characteristics, treatment strategies, and follow-up of the patients are summarized in Table 1 . [ 1 , 2 , 5 , 6 , 10 , 14 - 16 , 18 - 21 , 23 , 24 , 27 , 30 , 31 , 37 , 38 , 42 - 47 , 50 - 52 , 54 , 55 , 57 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The demographic, clinical characteristics, treatment strategies, and follow-up of the patients are summarized in Table 1 . [ 1 , 2 , 5 , 6 , 10 , 14 - 16 , 18 - 21 , 23 , 24 , 27 , 30 , 31 , 37 , 38 , 42 - 47 , 50 - 52 , 54 , 55 , 57 ]…”
Section: Resultsmentioning
confidence: 99%
“…e demographic, clinical characteristics, treatment strategies, and follow-up of the patients are summarized in Table 1. [1,2,5,6,10,[14][15][16][18][19][20][21]23,24,27,30,31,37,38,[42][43][44][45][46][47][50][51][52]54,55,57] e mean age of the patients was 48.2 years (range 30-72). In an article, one patient was described as a "teenager" but was not used for statistical evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…Surgery was generally performed on a semi-elective basis, following initial medical or endovascular management. No recurrent clinical characteristics were noted in those selected for surgical intervention, however, there appears to be a trend for surgical management as a definitive treatment choice in recurrent and/or severe ischaemic disease4–30 (online supplemental table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with this syndrome can also experience irritation of the sympathetic chain when rotating their neck, causing pain in the distribution of the carotid artery 2. Although more commonly seen in patients with connective tissue disorders and trauma, ICA dissection with acute ischaemic events secondary to stylocarotid Eagle’s syndrome has been described in a growing number of case reports 4–30. These cases share similar clinical presentations, however, given the rarity of the condition, there is no clear consensus on its definitive management.…”
Section: Introductionmentioning
confidence: 99%
“…24,34 A review of the literature revealed 15 cases of ICA dissection due to Eagle syndrome, which were treated with styloidectomy (Table 1). 1,3,4,7,14,15,20,24,[32][33][34][35] The median age at presentation was 46 years (interquartile range 41-55 years), and 11 (73%) of 15 patients were male. Three cases noted possible triggers, two of which were related to neck motion, whereas the third case occurred in a patient with a recent tooth extraction with tonsillar swelling.…”
Section: Observationsmentioning
confidence: 99%